L’inceste : filiations, transgressions, identités. Avec Spinoza et Freud - Isabelle Sgambato-Ledoux (Astérion)
Incest, as the acting of transgression and incestuality, as a psychic reality implying a narcissistic and alienating seduction, result of a causality explored by Spinoza and Freud, each in their own way. Founded on the main principles of their respective approach, the confrontation of their analyses of the individuation process, of filiation and of transgression, leads to each doctrine’s shedding light on the other. Then, the theoric points of convergence and the differences clearly appear. This confrontation also allows the theoric reconstitution of the genesis and of the nature of incest in its three main forms : as an object of social prohibition, as psychic incest and as enacted incest. Far from being the effect of sexual desires paving the way to a transgression of the law, incest is fostered by the very absence of the law and by the survival of too intense links that show at the same time the difficulties and the immaturity of the individuals they bind.